Determining distribution of elements in surface sediment, soft tissue and shell of Cerithidea obtusa Lamarck using nuclear and atomic techniques - Krishnan, Kumar (2015)
Mangrove forests found in the coastal areas of tropical countries are the primary productive ecosystems for marine life and increasingly suffer environmental degradation due to antrophogenic sources. Therefore, it is of significant to evaluate the degree of contamination in the mangrove ecosystems to identify whether it is a health risk for consumption of marine animals found in these areas. The current study involved the determination of concentrations of heavy metals, major and trace elements, and rare earth elements in the surface sediments and the soft tissues and shell of cerithidea obtusa collected from ten locations of mangrove areas along the west coast of Peninsular Malaysia. The Instrumentation Neutron Activation Analysis (INAA) and Atomic Absorption Spectrometry (AAS) techniques were used for this purpose. Several methods were used to evaluate the level of pollution in the sediments. Biota-sediment accumulation factor (BSAF) used to estimate of proportion in which metal occurs in the living organism and in associated sediment and hazard Risk index (HRI) estimated to identify any unlikely adverse human health effects from consumption of contaminated seafood. In the present investigation the order of accumulation of the heavy metal concentration in the surface sediments and the soft tissues and shell of cerithidea obtusa was Mn> Zn> Cr> Pb> As> Ni> Cu> Cd, Mn> Zn> Cu> Ni> Cr> As> Pb> Cd and Mn> Zn> Ni> Cu> Pb> Cr> As> Cd respectively. The highest enrichment factor was 9.18 (As) and the lowest was 0.21 (Cu) in the sediments. Contamination factors, degree of contamination (Cd), modified degree of contamination (mCd) and pollution level index (PLI) of all the heavy metal fall in the range of 0.13 - 1.90, 4.26 – 11.78, 0.70 – 1.47 and 0.42 – 1.18 respectively in the sediments. The highest geoaccumulation index was found in Zn with index 1.37 from location L5. Ecological factor and risk index varied in range 0.36 - 66.00 and 19.61 – 98.40 respectively in the sediments. The lowest health risk index was 0.010 (Cd) and the highest was 7.43 (Mn) based on the total concentration of elements in the soft tissues of cerithidea obtusa. Great concern must be given to the Mn especially at L5 due to HRI value seven times greater than unity. The results of this study supporting the L5 (Juru, Penang) is one the contaminated area as mentioned previously by other studies. BSAF of heavy metal in the soft tissues and shell of cerithidea obtusa ranged from 0.034 to 22.30 from 0.012 to 2.35 respectively. The total concentrations of REEs (Ce, La, Dy, Sm, Eu, Lu, Tb and Yb) in sediments samples ranged from 0.35 to 117.4 mg/kg. The geochemical behavior of REEs in surface sediments and normalized pattern (chondrite and shale) has been studied. Enrichment factor of REEs varied in the range from 0.75 to 6.75. The indicator ratios of La/Yb and Eu/Sm varied from 3.89 - 18.49 and 0.06 - 0.20 respectively. The Ce/La ratio was calculated and varied from 1.96 to 3.17. From the enrichment pattern can be concluded that LREE > HREE as the uptake sequence of the REE as in the mangrove sediment samples. No REEs was found in the soft tissues and shell of cerithidea obtusa. In the present investigation the order of accumulation trace elements in the sediment, soft tissues and shell of cerithidea obtusa was Ba> V> Ga> Cs> Hf> Sc> Ta> Co> Sb and Co > Sc respectively. The mean concentration of Co and Sc (other elements not detected) on the soft tissues and shell of cerithidea obtusa ranged from 0.83 to 6.94 and 0.12 to 2.39 mg/kg respectively. The enrichment of trace elements varied in range from 0.41 to 20.76 in the sediments. Contamination factors, Degree of contamination (Cd) and modified degree of contamination (mCd) of all the trace element fall in the range of 0.10 - 3.98, 5.77-11.49 and 0.64-1.36 respectively in the sediments. The highest geoaccumulation index was found in Ta (1.41) from location L6. BSAF of in the soft tissues and shell of cerithidea obtusa ranged from 0.01 to 0.94 and 0.03 to 0.14 respectively. The major element concentration in the sediment was in the order of Al>Fe>Na>Mg>K>Ca>Ti>Rb. The mean concentrations of Ca, Fe, K, Mg, Na and Rb on the soft tissues of cerithidea obtusa ranged from 11349 to 55815, 652 to 6284, 7561 to 13327, 6010 to 11595 and 0.99 to 30.6 mg/kg respectively. On the other hand, the mean concentrations of Ca, Fe, K, Mg, and Na (Rb not detected) on the shell of cerithidea obtusa ranged from 138509 to 403444, 209 to 1008, 256 to 1307, 315 to 503 mg/kg respectively. The enrichment factor of major elements ranged from 0.53 to 5.92 in the sediments. Geo-accumulation index was found highest in location L5 with index 1.27 (Na). BSAF of major elements in the soft tissues and shell of cerithidea obtusa ranged from 0.03 to 8.05, and 0.01 to 73.58 respectively.